2003
DOI: 10.5650/jos.52.167
|View full text |Cite
|
Sign up to set email alerts
|

Suspension Polymerization of Styrene Monomer without Emulsifier and Initiator.

Abstract: Ultrasonic waves were used to perform suspension polymerization of styrene monomer in the absence of both emulsifier (surfactant) and polymerization initiator. Styrene monomer was ultrasonically dispersed as oil droplets at 40 kHz after being added dropwise into water. Polymerization of the monomer in the droplets was initiated with the radical species from water as the polymerization initiator generated by irradiation with a high frequency ultrasonic wave at 200 kHz on the surfactant-free (styrene monomer/wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It is in contrast to a unimodal but wide size distribution which resulted from intense irradiation at low frequencies, such as in the range 0.05-2.65 µm in the presence of surfactant. 3 We suppose that the observed monodispersity of polymers synthesized at 200 kHz initiation with the present experimental setup 23 would be partly due to the monodispersed generation of monomer droplets by the submegasonic wave applied, in addition to the radical chain kinetics so far concerned. Consequently, high frequency or megasonic irradiation significantly contributed to the stabilization of oleic acid droplets over a short and long period.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…It is in contrast to a unimodal but wide size distribution which resulted from intense irradiation at low frequencies, such as in the range 0.05-2.65 µm in the presence of surfactant. 3 We suppose that the observed monodispersity of polymers synthesized at 200 kHz initiation with the present experimental setup 23 would be partly due to the monodispersed generation of monomer droplets by the submegasonic wave applied, in addition to the radical chain kinetics so far concerned. Consequently, high frequency or megasonic irradiation significantly contributed to the stabilization of oleic acid droplets over a short and long period.…”
Section: Resultsmentioning
confidence: 84%
“…The effect becomes more significant for smaller particulates and at higher frequencies, so that its application has widely been developed as precision or megasonic cleaning in semiconductor wafer manufacturings. Meanwhile, megasonic waves as well as being a high power source at low frequencies are known to induce sonochemical effects including radical formation and molecular degradation, which have been used to open up a new field in sonochemistry, such as the sonolysis of methanol at 1 MHz, a new synthetic or degradation strategy of compounds, , etc. While ultrasonic initiation has also been developed for radical polymerization with high-power probes at 20 kHz in the pioneering studies, submegasonic baths can give a more gentle condition for the initiation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, suspension polymerization with oil-in-water systems is less detrimental to the environment as it uses less organic solvent than inverse suspension polymerization. Okudaira et al reported a preparation method for hydrophobic polystyrene (PSt) microparticles by a surfactant-free suspension polymerization, 27 but there are no such reports on hydrophilic polymer microparticles, owing to the dissolution of hydrophilic monomers in water. Thus, it is challenging to establish a protocol toward hydrophilic polymer microparticles by surfactant-free suspension polymerization with an oil-in-water system.…”
Section: Introductionmentioning
confidence: 99%
“…Using ultrasonic waves to perform suspension polymerization of styrene monomer in the absence of both emulsifier and initiator, Gen et al21 reported that the particle size obtained from TEM and dynamic light scattering was on the order of several tens of nanometers. Tuin and Stein22 investigated the adsorption of an ionic surfactant on polystyrene particles in the presence of a cosurfactant.…”
Section: Introductionmentioning
confidence: 99%